RECURRENT CHRONIC CONJUNCTIVITIS DUE TO RAOULTELLA ORNITHINOLYTICA: A RARE CASE REPORT - Vesela Ivancheva; Aleksandar Lyubenov; Nikolay Ivanov (Science & Research)

(untitled)
Aim This brief report of a rare case of conjunctivitis caused by Raoultella ornithinolythica provides a description of possibly the first documented case of this eye infection in Bulgaria. Materials and Methods Atypical case of an 81-years old patient with a history of chronic purulent conjunctivitis, non-responsive of topical treatment, was presented in our clinic. The laboratory result of conjunctival swab was R. ornithinolythica positive. Results This organism causes a non-specific purulent conjunctivitis that seems to have a benign, but chronic course and tends not to be responsive to a topical antibiotic treatment. Systemic treatment with amoxicillin and clavulanic acid was effective. Conclusions The possibility of atypical organisms must be considered when managing chronic infective conjunctivitis. Conjunctival swabs should be obtained and topical treatment switched when initial empirical therapy fails. If necessary, systemic therapy should be considered.